2020
DOI: 10.1016/j.fbio.2020.100714
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of ginger oil in alginate-based shell materials

Abstract: Hydrogels consisting of a blend of sodium alginate and k -carrageenan aqueous solutions were prepared using Ca 2+ as the gelling agent in a shell material formulation for encapsulation of food-grade ginger oil. A preliminary study on the rheological and textural behavior of two hydrogels prepared from (1) alginate water solution and (2) alginate blended with k -carrageenan in water showed that the latter produced gels with higher values of elastic and viscous moduli and gel strength, related to added mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Therefore, the CaCl 2 concentration had an influence on the strength of the capsules. Other authors have found that the strength of the sodium alginate gel increases with the CaCl 2 concentration, as the formation of stronger and more crosslinked bound gels is favoured due to the presence of more available Ca 2+ ions [35,36]. Besides that, the chitosan coating provided extra coverage in the capsules, which may influence the ability of their structure to make them increase probiotic viability [28] and to withstand the digestive conditions and help the probiotic to survive and reach the lower gastrointestinal tract (GIT).…”
Section: Capsule Characterizationmentioning
confidence: 95%
“…Therefore, the CaCl 2 concentration had an influence on the strength of the capsules. Other authors have found that the strength of the sodium alginate gel increases with the CaCl 2 concentration, as the formation of stronger and more crosslinked bound gels is favoured due to the presence of more available Ca 2+ ions [35,36]. Besides that, the chitosan coating provided extra coverage in the capsules, which may influence the ability of their structure to make them increase probiotic viability [28] and to withstand the digestive conditions and help the probiotic to survive and reach the lower gastrointestinal tract (GIT).…”
Section: Capsule Characterizationmentioning
confidence: 95%
“…Atencio et al 56 prepared hydrogels using a combination of sodium alginate and κ-carrageenan aqueous solutions in a shell material formulation to encapsulate ginger oil. In the encapsulation of ginger oil, four formulations of the shell material were prepared from 1% w/w alginate solution and from a blend of 1% w/w alginate solution with 1.5% w/w κ-carrageenan (at 80 : 20 v/v ratio) with and without incubation in a 0.1 w/w chitosan solution as a final coating in a two-stage capsule hardening procedure.…”
Section: Encapsulation Of Ginger Bioactive Compoundsmentioning
confidence: 99%
“…Besides, the ginger oil extracted from capsules with alginate and κ-carrageenan, along with chitosan as the final coating, showed the lowest content of oxidation products throughout the storage period (15 days), suggesting better protection of ginger oil. 56 In the Borcan et al 57 study, polyurethane (PU) with pure ginger extract (GE) was obtained using a poly-addition process combined with a simultaneous emulsification. The particles presented almost neutral pH values and low water solubility.…”
Section: Encapsulation Of Ginger Bioactive Compoundsmentioning
confidence: 99%
“…According to the properties, these gels are similar to solid materials, but they consist of 99.0–99.5% water. This biopolymer has several properties (low price, easy to use, biodegradability, and biocompatibility), which makes it a suitable material for encapsulation of extracts [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%